Push-Me Pull-You: Comparative Advertising in the OTC Analgesics Industry - Simon P. Anderson; Federico Ciliberto; Jura Liaukonyte; Régis Renault (Center for Economic Studies and ifo Institute (CESifo), 2015)
We derive equilibrium incentives to use comparative advertising that pushes up own brand perception and pulls down the brand image of targeted rivals. Data on content and spending for all TV advertisements in OTC analgesics enable us to construct matrices of dollar rival targeting and estimate the structural model. Using brands. optimal choices, these attack matrices identify diversion ratios, from which we derive comparative advertising damage measures. We find that comparative advertising causes more damage to the targeted rival than benefit to the advertiser. We simulate banning comparative advertising to find industry profits rise.
Keywords: L13; M37; L65; 330; comparative advertising; advertising targets; diversion ratios; attack matrix; push and pull effects; analgesics